VEGA, L. (Ed.) (2014): Empires, Post-Coloniality and Interculturality. New Challenges for Comparative Education (Rotterdam-Boston-Taipei: Sense Publishers) - González López, Víctor (Revista Española de Educación Comparada, 2015)
Recensión a cargo de Víctor González López